The royal road to the obesity: a case report of food addiction - Kandeğer, Ali; Bozkurt, Hasan (Journal of Dependence, 2016)
Increasing prevalence of obesity in the world and increasing role of processed foods in daily life has led to become the focus of the food addiction. In recent years, the animal studies and human brain imaging studies demonstrated the neurobiological and behavioral similarities between drug addiction and food addiction. Here, we aim to present a 13 year-old, female, 7th grade student who applied with complaints of anger and irritability and shows serious addictive behaviors of chocolate. Our patient with increasing chocolate consumption in the last two years was using atomoxetine 60 mg/day with ADHD. She gradually needs to more chocolate to be satisfied. She has complained of nervousness, irritability and serious chocolate-seeking behavior during chocolate deprivation. She gained weight in proportion to the increase in chocolate consumption. Her daily diet was increasingly deteriorated. We used behavioral approach and sertraline in her treatment and were observed that partially benefit from treatment. Combined data from retrospective accounts of adults and prospective observations of youth indicates that juveniles with ADHD are at increased risk for cigarette smoking and substance abuse and behavioral addiction such as internet addiction, gambling and sex addiction during adolescence. Recognition of the food addiction is important to fight against obesity, strengthening the treatment of choice in the food addiction and take political preventions against food addiction are becoming inevitable.
Keywords: Addiction; attention deficit hyperactivity disorder; obesity